ANALISIS PENGARUH PRAKERIN, MINAT KERJA DAN LINGKUNGAN SEKOLAH TERHADAP KESIAPAN KERJA SISWA DI SMKN 4 GOWA - Yoldis Hasrianti I; Yunus Tjandi; Lu'mu (UNM Journal of Technology and Vocational, 2021)
The purpose of this study was to determine the level of work interest, the influence of the school environment and work readiness as well as the influence of industrial work practices (prakerin), work interest, and school environment on work readiness of class XII students of SMK Negeri 4 Gowa in the 2020/2021 school year partially or simultaneously. This type of research is a quantitative analysis research and the sampling technique uses a proportional cluster random sampling technique which is determined using the Krejcie table with a sample size of 73 respondents. Data collection methods use observation, documentation, and questionnaires. The results showed that 46.5% of students had a high category of apprenticeship scores, 84.9% of students with a high level of work interest, 93.2% of students admitted that the school environment affected work readiness and 89% of students had a high level of work readiness. . Furthermore, partially internship has an effect on student work readiness, work interest has a significant effect on student work readiness by 14.82% and the school environment has a significant effect on student work readiness by 39.0. Simultaneously internship, work interest and school environment have a significant effect on readiness student work amounted to 51.4%..